Osteometabolic changes in patients under antineoplastic treatment: scoping review - Lucas Dalvi Armond Rezende; Davi de Souza Catabriga; Karielly Gasperazzo Pansini; Mateus Gonçalves Prata dos Reis; Paula de Souza Silva Freitas; Bruno Henrique Fiorin (Hospital de Clínicas de Itajubá, 2023)
Objective: To summarize the main evidence regarding osteometabolic changes in patients undergoing antineoplastic treatment. Methods: This is a scoping review, following the methodology of the Joanna Briggs Institute, using PubMed/MedLine, Cochrane Library, LILACS, The British Library, and Google Scholar. This review is registered in the Open Science Framework. Results: Many antineoplastics affect bone architecture by reducing its density, such as selective estrogen receptor modulators, aromatase inhibitors, androgen deprivation therapy, and glucocorticoids. To avoid such outcomes, treatment and prevention can be achieved by calcium and vitamin D supplementation, physical exercise, use of bisphosphonates, denosumab, and selective estrogen receptor modulators. Conclusion: people at a higher risk of developing cancer also have a higher risk of osteopenia and osteoporosis when the process is already established and undergoing antineoplastic treatment because of the grouping of risk factors. The need for bone densitometry in patients undergoing cancer treatment to prevent and promote bone health in these patients is evident, in addition to more research with a high level of evidence to support such use.